Utilizing the Potential of Local Wisdom and Infrastructure Development of Old village of Tiangwangkang, Tembesi Sub-District, Batam City - Yandi, Delpra; Rakhman, Kurnia; Martan, Viven; Sidabutar, Yuanita FD (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Indonesia is a country located in Southeast Asia and has more than 17,000 islands in it. One of the provinces in the form of islands is the Riau Archipelago Province which is close to Singapore and Malaysia, so that many tourists also visit the province, such as Batam City. In Batam City there are several tourist objects such as the Batam Botanical Garden, Welcome to Batam, and also Ocarina Park. Apart from tourist attractions in the city center, Batam City also has beach tourism destinations such as Melayu Beach, Melur Beach and many other beaches. Old village can also be an option for tourists to visit because there are many cultural values ​​of local wisdom that are still maintained and preserved in it. One of them is the Old village of Tiangwangkang which is in the Tembesi Village, Sagulung District. old village of Tiangwangkang has the potential to become a tourist village because it has a strategic area, which is close to the beach and also close to the Barelang Bridge. However, there are several problems in the area such as road problems, street lighting, and also several other public facilities to support the accessibility of the community and tourists later. Therefore, it is necessary to develop infrastructure and also arrange it so that the village is worthy of being a tourist village. This research uses a descriptive method as well as a potential analysis to see the potential of this region. Old village of Tiangwangkang has the potential to become a tourist village because it has local wisdom that is still maintained and has beautiful views. However, to become a tourist village that is appropriate and can prosper the local community, it is necessary to develop infrastructure and arrange it so that the old village of Tianwangkang can become a tourist destination that is comfortable and worth visiting.